A systematic Literature Review of Internet of Things for Higher Education: Architecture and Implementation - Eddy Soeryanto Soegoto; Herman Soegoto; Dedi Sulistiyo Soegoto; Suryatno Wiganepdo Soegoto; Agis Abhi Rafdhi; Herry Saputra; Dina Oktafiani (Universitas Pendidikan Indonesia, 2022)
The objectives of this paper are to analyze the implementation and architecture of the Internet of Things (IoT) from previous studies, specifically in the world of higher education; offer recommendations for future research, as well as strengthen the theory of IoT architecture that already exists in higher education. This study employed a systematic literature review (SLR) with data collection utilizing Funnel Diagrams to select articles based on their relevance to the research question. The three publisher databases (Scopus, Emerald, and EBSCO) and index journals were utilized in the search for articles. A total of 1,200 articles were gathered from these three sources, with distributions of up to 800 in Scopus, 150 in Emerald, and 250 in EBSCO. The findings demonstrate that the existing IoT architecture has a more sophisticated model than the fundamental idea, which has three layers, implying that using IoT in education may have a significant influence on user convenience. This is due to the increasingly complicated requirements of higher education's many business procedures. This study serves as an inspiration and reference for future research for higher education institutions that include the Internet of Things in their implementation to build an efficient teaching and learning environment.